Tanggung Jawab Jabatan Dan Tanggung Jawab Pribadi Dalam Penggunaan Diskresi - Asyikin, Nehru; Setiawan, Adam (UI Scholars Hub, 2020)
Discretion is part of the authority to act freely by government officials to ensure the implementation of public services. However, the discretionary rules inherent in the office when it must be immediately to act without written law creates a conflict about the government must be based on the law. On the other hand the need for discretion becomes a polemic regarding job responsibilities and personal responsibility in the use of discretion, which parameters of use sometimes cause harm to society. The results of the study show that the implications of using discretion in the actions of officials that are used in the interest of public services turn out to cause losses to the state and society. The use of discretion is even used as a tool for personal gain and raises abuse of authority which results in violating the laws and regulations, contrary to the principles of law, illegal acts and AAUPB.